Dual RNA-Seq analysis unveils the multifaceted mechanisms of Trichoderma hamatum in the biological control of Fusarium graminearum, the causal agent of wheat fusarium head blight - Cheng, Yunqing; Wang, Shuai; Zhao, Shuang; Yang, Siqi; Li, Yuqing; Wang, Bing; Zhang, Furan; He, Hongli; Liu, Jianfeng (Frontiers in Microbiology, 2026)
BackgroundFusarium head blight (FHB), caused by Fusarium graminearum (Fg), is a devastating wheat disease leading to substantial yield losses. Effective biocontrol strategies are urgently needed.ObjectiveThis study aimed to investigate the antagonistic potential of Trichoderma hamatum (Th) against Fg and elucidate its transcriptional mechanisms.MethodsAntagonistic activity was assessed via dual-culture and pot experiments with wheat seedlings under four treatments: control (CK), Th, Fg, and dual inoculation (Th-Fg). Transcriptome sequencing (RNA-seq) data were aligned to the genomes of Fg, Trichoderma guizhouense (as a proxy for Th), and Triticum aestivum to analyze gene expression changes.ResultsBoth assays showed Th strongly inhibited Fg growth. RNA-seq revealed that under Th pressure (Fg vs. Th–Fg), Fg exhibited widespread transcriptional suppression, with 608 DEGs downregulated and enriched in carbohydrate metabolism, indicating disrupted nutrient acquisition. Th itself showed minimal transcriptional changes (Th vs. Th–Fg), suggesting a resource-efficient strategy. Fg infection (CK vs. Fg) suppressed wheat photosynthesis and carbon metabolism, while Th inoculation (CK vs. Th) primed defense pathways. In the dual inoculation, Th alleviated Fg-induced suppression and enhanced wheat defense and physiological gene expression. qRT-PCR validated the RNA-seq reliability.ConclusionTrichoderma hamatum suppresses Fg via a tripartite mechanism: direct antagonism by impairing pathogen metabolism, priming wheat immunity, and mitigating physiological damage. This study provides molecular insights for using T. hamatum as a potent biocontrol agent against FHB.